2014
DOI: 10.3171/2013.9.peds13257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex on symptoms and return to baseline in sport-related concussion

Abstract: Object Sport-related concussions (SRCs) among youth athletes represent a significant public health concern. Prior research suggests that females fare worse symptomatically after an SRC. The authors aimed to assess sex differences in number, severity, and resolution of postconcussive symptoms using reliable change index (RCI) methodology applied to days to return to symptom baseline. Methods Between 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 38 publications
7
83
2
Order By: Relevance
“…Young, female athletes reported higher symptom scores and took longer to become symptom free than males following sports-related concussions [26] . Similarly in another study, females were found to report a greater severity of symptoms after concussion and to take longer to return to baseline symptom levels than males while symptom profiles were not significantly different between the sexes [27] .…”
Section: Discussionmentioning
confidence: 57%
“…Young, female athletes reported higher symptom scores and took longer to become symptom free than males following sports-related concussions [26] . Similarly in another study, females were found to report a greater severity of symptoms after concussion and to take longer to return to baseline symptom levels than males while symptom profiles were not significantly different between the sexes [27] .…”
Section: Discussionmentioning
confidence: 57%
“…For example, the biomechanics and amount of RHI experienced by former NFL players may differ from that of athletes in other high-risk sports, such as soccer and ice hockey. Additionally, developmental trajectories [37][38][39] and outcomes 74 following mTBI differ between males and females; therefore, these results also may not apply to females exposed to RHI during youth. Second, it is not known whether continued exposure to RHI in adolescence and adulthood influences the brain's ability to recover following childhood exposure to RHI.…”
Section: Stamm Et Almentioning
confidence: 86%
“…[44][45][46][47][48] Many hypotheses have been put forth to explain the sex difference in elevated and prolonged symptoms. Some have speculated that sex differences in head size or neck musculature may contribute, 49 while others have argued that the findings can be explained by women's and girls' more forthcoming reporting style.…”
Section: Rabinowitz Et Almentioning
confidence: 99%